The Influence of Product Innovation and Digital Marketing on MSME Performance Through Risk Taking as an Intervening Variable - Istiawanti, Naning; Qomariah, Nurul; Nursaid (Yayasan Sinergi Kawula Muda, 2025)
The issuance of Law Number 20 of 2008 concerning MSMEs which was revised again into Government Regulation Number 7 of 2021 regulating the convenience, protection and empowerment of MSMEs is considered to be less than optimal. Many millennials open MSMEs but do not last long due to discontinuous demand, capital constraints and limited raw materials. Several policies have been taken by the government to protect MSMEs to develop and survive, but they have not run optimally as expected. Therefore, this study was conducted with the aim of directly or indirectly determining the influence of product innovation and digital marketing on MSME performance through risk taking as an intervening variable on MSMEs in Banyuwangi Regency. This study is a quantitative study with a research population of MSMEs selling food in Banyuwangi Regency. The population in this study were MSMEs in Banyuwangi Regency who received assistance from the Industry, Trade and Cooperatives Service totaling 1263 MSMEs. The sampling technique used nonprobability sampling with a purposive sampling technique to obtain a sample of 125 MSMEs. The sample of this study is MSMEs in Banyuwangi Regency that sell food and use digital marketing with a population of 125 business units. The analysis technique used is the Structural Equation Model (SEM) using WarpPLS 7.0. The results of data analysis show that the product innovation variable does not have a significant effect on risk taking, digital marketing has a significant effect on risk taking, product innovation has a significant effect on MSME performance, digital marketing has a significant effect on MSME performance, risk taking does not have a significant effect on MSME performance. Indirectly, product innovation and digital marketing have a significant effect on MSME performance through risk taking.